БЎЛАЖАК ТАРИХ ЎҚИТУВЧИЛАРИДА ИЖОДИЙ ФИКРЛАШНИ РИВОЖЛАНТИРИШНИНГ АСОСИЙ КОМПОНЕНТЛАРИ - Ярматов, Р.Б. (SCIENCE and SOCIETY, 2019)
The article teaches a future history teacher to develop students' ability to work with historical sources and literature, and to provide students with access to additional literature and resources, to historical and artistic works, and the ability to communicate to the media on the basis of their knowledge of history.
Keywords: worldview; spirituality; self-esteem; talent; abilities; observation; modern knowledge; human factor